Educational Partnership in Ensuring a Digital Diet during the Time of Home Education - Barabasi, Tunde; Stark, Gabriella (Technium Social Sciences Journal, 2022)
The epidemiological situation has brought about changes in various segments of preschool education, especially during the closure of kindergartens. Early childhood teachers had to re-evaluate their educational approach and practices, including on one hand the activities they were to offer children studying online and on the other hand finding a way to cooperate with parents in order to create the necessary conditions for the activities to be carried out. The purpose of the present study is to shed light on the concepts of educational partnership and digital diet, as well as reflect on the results of a survey research which presents the indicators and areas of partnership between early childhood teachers and parents striving to ensure preschoolers’ digital diet in the online educational and learning environment. Data was gathered from Hungarian early childhood teachers in Romania (N=403) and preschoolers’ parents (N=323). Results show an intensified educational partnership between early childhood teachers and parents during the home education period. When it comes to the digital diet we can speak of a more intense cooperation in defining time limits and a more relaxed approach to determining the content. Results also show that parents’ involvement can be increased with the help of the right strategies on the part of early childhood teachers. On the whole, online education had a positive effect on the educational cooperation, both in theory and practice, though there are some areas that need further optimization.